Effects of adding flaxseed milk coproduct and okara on the quality and glycemic response of Chinese steamed bread - Yan Tang; Yaqiong Pei; Jiahui Wang; Haichao He; Mingkai Sun; Yashu Chen; He Liu; Hu Tang; Qianchun Deng (Oil Crop Science)
Flaxseed milk coproduct (FMC) is a by-product of flaxseed milk. Okara is a by-product of processed soybean products. In this study, we investigated the quality of dough and Chinese steamed bread (CSB) with the addition of FMC and okara. We also examined the in vitro starch digestibility, expected glycemic index (eGI), starch crystallinity, and short-range order structure of CSB. The results showed that FMC and okara decreased the dough fluidity, formed a dense structure, and enhanced the mechanical properties of the dough. FMC and okara increased the hardness, gumminess, and chewiness of the CSB, while decreasing its cohesion and elasticity. The addition of FMC and okara improved the nutrient content of CSB and reduced the eGI from 75.86 to 51.56. FMC and okara altered the multiscale structure of starch, effectively shielding the amylase site of action, and limited the interaction between amylase and starch. This study provides a reference for the high-value utilization of oilseed processing by-products.